(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article notes the traditions of ceramics and traditions that have been going on for centuries, as well as the traditions of the teacher and apprentice. The main attention is paid to the aspects of the traditional material culture of the people of the Valley, various rituals in the daily work of the master potters of the Fergana Valley, the processes of mastery of the khalas.